2010
DOI: 10.1016/j.jtcvs.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring of function of autologous engineered pulmonary valve

Abstract: We demonstrate autologous engineered tissue valved conduits that function well at implantation, with subsequent monitoring of dimensions and function in real time by magnetic resonance imaging. In vivo valves undergo structural and functional remodeling without stenosis, but with worsening pulmonary regurgitation after 6 weeks. Insights into mechanisms of in vivo remodeling are valuable for future iterations of engineered heart valves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
131
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 18 publications
2
131
2
Order By: Relevance
“…Proper valve closure remains a challenge for heart valve tissue engineering, as regurgitation has been reported in several studies (Flanagan et al, 2009;Gottlieb et al, 2010). Regurgitation is mainly caused by cell-mediated retraction of the leaflets (Dijkman et al, 2012;van Vlimmeren et al, 2011van Vlimmeren et al, , 2012, and to ensure valve closure, these contractile cellular forces should be counteracted by the pressure applied to the valve during diastole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper valve closure remains a challenge for heart valve tissue engineering, as regurgitation has been reported in several studies (Flanagan et al, 2009;Gottlieb et al, 2010). Regurgitation is mainly caused by cell-mediated retraction of the leaflets (Dijkman et al, 2012;van Vlimmeren et al, 2011van Vlimmeren et al, , 2012, and to ensure valve closure, these contractile cellular forces should be counteracted by the pressure applied to the valve during diastole.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have demonstrated the in vivo functionality of tissue-engineered heart valves (TEHVs) in animal models (Hoerstrup et al, 2000;Flanagan et al, 2009;Gottlieb et al, 2010;Schmidt et al, 2010). However, also this approach faces a number of challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, bioreactor systems inducing mechanical conditioning and flow profiles have improved in vitro tissue formation (Flanagan et al 2007;Mol et al 2005;Kortsmit et al 2009;Ruel and Lachance 2009;Syedain and Tranquillo 2009). Moreover, in vivo animal studies have demonstrated the feasibility of heart valve tissue engineering, showing remodeling into native-like structures Sodian et al 2000;Stock et al 2000;Sutherland et al 2005;Gottlieb et al 2010;Schmidt et al 2010;Flanagan et al 2009). However, there are still some challenges that need to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still some challenges that need to be overcome. One of those challenges is cell-mediated leaflet retraction, causing regurgitation in vivo (Flanagan et al 2009;Gottlieb et al 2010;Syedain et al 2011). In general, this regurgitation has been neglected and reported to be only mild.…”
Section: Introductionmentioning
confidence: 99%
“…In most TEHV implant studies to date, 2,5,8,21,22,26 autologous animal cells were used to fabricate the implant. Since the transition from an animal cell source to human cells in developing a TEHV with comparable properties can be problematic, our approach was to develop the VE with a convenient human cell source and utilize immunosuppression to evaluate the VE performance in an animal model, recognizing that tissue remodeling may be influenced by the drugs.…”
Section: Introductionmentioning
confidence: 99%